The Effectiveness of Red Fruit Oil (Pandanus conideus Lamk.) Emulgel on the Acceleration of the Incision Wound Healing Process - Fidia Rizkiah Inayatilah; Abdul Malik Guhir; Ria Ramadhani Dwi Atmaja (Majalah Obat Tradisional, 2022)
Incision wounds have a fairly high prevalence in Indonesia. Chemical treatment of incision wounds has adverse side effects, therefore alternative treatment with natural ingredients is needed, namely using red fruit oil as the basic ingredient. The purpose of this study is to determine the effectiveness of red fruit oil (Pandanus conoideus Lamk.) gel emulsion on the healing process of incision wounds in males both macroscopically and microscopically. This is an experimental laboratory study. The study design used was true experimental with a post-test-only control group design approach. The population consisted of 25 male mice which were divided into 5 groups, namely: (1) K- was a control group where the incision wound on the back was given a gel emulsion base; (2) K+ was the control group where the incision wound on the back was given Iodine Povidone ; (3) P1 is the treatment group where the incision wound on the back is given a 5% red fruit oil gel emulsion (F1); (4) P2 is the treatment group where the incision wound on the back is given a red fruit oil gel emulsion 10% (F2); (5) P3 was the treatment group where the incision on the back was given a 15% red fruit oil gel emulsion (F3). The treatment was given for 14 days. The data were then analyzed using the ANOVA test. The result showed that the administration of red fruit oil emulgel had a significant effect on the size of the incision wound on the 7th day (p=0.035) and the 14th day (p=0.005). Giving red fruit oil emulgel also had a significant effect on the thickness of the epithelium (p=0.000) and the number of fibroblasts (p=0.000). It can be concluded that the administration of red fruit oil emulgel affects the healing process of the incision wound both macroscopically and microscopically.